ACCOUNTING MEETS AI: THE INFLUENCE OF TECHNOLOGY READINESS AND HEDONIC MOTIVATION ON STUDENTS’ ADOPTION INTENTION - Ulfah Tika Saputri; Meilinda Dwi Anugrah; Kurnia Widya Oktarini; Devi Febrianti; Edy Firza (TECHNOBIZ : International Journal of Business, 2025)
This study aims to examine the mediating effect of hedonic motivation on the relationship between technology readiness and the intention to adopt AI technology in the learning process of accounting students at vocational higher education institutions. A purposive sampling technique was employed, resulting in 500 respondents who met the predefined criteria and were included as the study sample. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that technology readiness does not have a direct effect on the intention to adopt AI in the learning process. Instead, hedonic motivation serves as a mediating variable, linking technology readiness to the intention to adopt AI-based technology among accounting students in vocational higher education.